Predicting Posttraumatic Stress and Depression Symptoms Among Frontline Firefighters in China. Issue 1 (January 2021) - Shi, Junyi; Chen, Yaru; Li, Xiaohui; An, Yuanyuan
Abstract : Abstract: To investigate the prevalence and comorbidity rate of potential posttraumatic stress disorder (PTSD) and depression in frontline firefighters in China, as well as to analyze the related predictive factors for PTSD and depression, our study included 261 firefighters who completed assessments including the Demographic Data Forum, PTSD Checklist for DSM-5, Center for Epidemiological Studies Depression Scale, Chinese version of Perceived Stress Scale, and Perceived Social Support Scale. Among the participants, 1.9% and 11.9% were identified as having potential PTSD and depression, respectively. There was a 9.1% chance of comorbid PTSD among the depressed firefighters and a 60% chance of comorbid depression among the firefighters with PTSD. Perceived stress positively predicted both PTSD and depression; perceived social support negatively predicted both PTSD and depression. Whereas family exogenous support predicted both PTSD and depression, family endogenous support only predicted depression. In addition, PTSD was predicted by rank. Soldiers and sergeants demonstrated higher level of PTSD than officers. Future studies on mental health of firefighters should take factors like perceived stress, social support, and rank into consideration.